Diminished adherence and/or ingestion of virulent Mycobacterium tuberculosis by monocyte-derived macrophages from patients with tuberculosis (1998)
ABSTRACT: The interaction between the macrophage and Mycobacterium tuberculosis is mediated by a variety of macrophage membrane-associated proteins. Complement receptors have been implicated in the adherence of M. tuberculosis to macrophages. In the present work, the adherence and/or ingestion of M. tuberculosis H37Rv to human monocyte-derived macrophages (MDM) from patients with tuberculosis (TB) and healthy controls was measured by microscopical examination, [3H]uracil incorporation, and CFU. The adherence and/or ingestion was enhanced by fresh serum and inhibited by heat inactivation, EDTA treatment, and anti-CR1 and anti-CR3 antibodies. Comparison of MDM from TB patients and healthy controls showed that the former exhibited a significantly decreased capacity to adhere and/or ingest M. tuberculosis, as determined by the number of CFU and 3H incorporation. The expression of CR1 (CD35) and CR3 (CD11b/CD18) on MDM from TB patients and healthy controls, as determined by flow cytometry, did not show significant differences. These results suggest that the lower ingestion of M. tuberculosis by MDM from TB patients is not due to defects in complement receptors, and therefore, there might be other molecules involved in the adherence and/or ingestion process that render MDM from TB patients ingest less mycobacteria than those from healthy controls.